The Role of Schools in Controlling the Utilization of Smartphones as Learning Resources for Elementary School Students - Nur Azizah Rohmawati; Harun Joko Prayitno; Achmad Fathoni; Minsih; Choiriyah Widyasari (Universitas Pendidikan Ganesha, 2023)
Most students often misuse the importance of using smartphones in learning at school. One of the functions of a smartphone in learning is as a learning resource in supporting the learning process. This study aimed to analyze the role of schools in controlling the use of smartphones as a learning resource. This study uses a qualitative approach with an experimental design. Data collection techniques used include interviews and observation. Data collection instrument in the form of a questionnaire. Data analysis techniques used are editing, coding, and tabulation. The results showed that using smartphones by students as a learning resource to find solutions to questions whose answers were considered onerous, study material by watching learning videos, and understand the material that needed to be written in textbooks. The role of schools in efforts to control the use of smartphones by students is to make rules by prohibiting students from using smartphones during learning, facilitating technology-based learning by providing multimedia space, and imposing sanctions in the form of confiscation of students' smartphones if found using smartphones for negative things, and carrying out socialization to parents when asked to pick up the confiscated smartphone should be each of the parents. It was concluded that most students use smartphones to answer questions that are not in the book, and the school controls the use of students' smartphones by providing oversight.